A Multicenter Phase II Study of Gemcitabine, Capecitabine, and Bevacizumab for Locally Advanced or Metastatic Biliary Tract Cancer. (July 2018) - Iyer, Renuka V.; Pokuri, Venkata K.; Groman, Adrienne; Ma, Wen W.; Malhotra, Usha; Iancu, Dan M.; Grande, Catherine; Saab, Tanios B.
Abstract : Objectives: Vascular endothelial growth factor overexpression, seen in 42% to 76% of biliary tract cancers (BTCs), correlates with poor survival. We explored the safety/efficacy and potential biomarkers for bevacizumab in combination with gemcitabine-capecitabine in advanced BTCs. Patients and Methods: Inoperable stage III/IV BTC patients in our prospective study were given 1000 mg/m 2 of gemcitabine (on days 1, 8), 650 mg/m 2 of capecitabine (on days 1 to 14), and 15 mg/kg of bevacizumab (on day 1) in 21-day cycles. Circulating tumor cells and quality of life were assessed at baseline and before cycle 2 and 3. Results: In total, 50 patients with gallbladder cancer (22%), intrahepatic (58%), and extrahepatic (20%) cholangiocarcinoma, received a median of 8 treatment cycles for median treatment duration of 5.8 months. Common grade 3/4 toxicities were neutropenia (36%), thrombocytopenia (16%), fatigue (20%), infections (14%), and hand-foot syndrome (10%). There were 12 partial response (24%), 24 stable disease (48%) with clinical benefit rate of 72%. Median progression-free survival was 8.1 months (95% confidence interval, 5.3-9.9). Median overall survival was 10.2 months (95% confidence interval, 7.5-13.7). Circulating tumor cells were identified at baseline in 21/46 patients (46%), who had lower median overall survival compared with those without (9.4 vs. 13.7 mo; P =0.29). Patients with quality of life scores greater than the group median by the end of first cycle of treatment had improved survival compared with those who did not (13.3 vs. 9.4 mo; P =0.39). Conclusions: Addition of bevacizumab to gemcitabine/capecitabine did not improve outcome in an unselected group of patients with advanced BTC compared with historical controls. The selective benefit of vascular endothelial growth factor inhibition in BTC remains to be explored.